Inorganic Acid Anions in Distilled Alcoholic Beverages: Capillary Electrophoresis with Conductometric Detection - Nataliya V. Shelekhova; Irina M. Abramova; Tamara М. Shelekhova (Техника и технология пищевых производств)
Distilled alcoholic drinks are popular all over the world. Monitoring the quality and safety of such drinks requires modern instrumental methods. Chemical composition of alcoholic beverages has become focus of numerous experimental and theoretical publications. However, this area remains understudied. This research provided an experimental confirmation of the capillary electrophoresis as a prospective method for determining anions in alcoholic beverages. The study involved model solutions and 30 samples of distilled alcoholic beverages purchased by random sampling from a retail chain. The chemical analysis relied on a PrinCE 560 capillary electrophoresis system equipped with a conductometric detector. The study revealed the working parameters for electrophoretic analysis that provided a selective qualitative and quantitative test of five target analytes in 9 min. The optimal composition of the buffer solution and the optimal electrolyte ratios were 30 mmol/dm3 L-Histidine and 30 mmol/dm3 2-(N-Morpholino) ethanesulfonic acid Monohydrate. The correlation between the peak area and the mass concentration was at 0.1–10 mg/dm3 for the target analytes. The approach proved effective in determining chloride, nitrate, sulfate, fluoride, and phosphate ions in whiskey, rum, tequila, moonshine, grain, and rum distillates. The study also included a comparative analysis of the qualitative and quantitative anion profiles in whiskey samples from different countries. All the samples contained 0.22–52.74 mg/dm3 chlorides, 0.60–0.06 mg/dm3 nitrates, 0.25–17.59 mg/dm3 sulfates, and 0.75–12.70 mg/dm3 phosphates. Research prospects include a metrologically certified method to identify the anion composition of organic and inorganic acids in distilled alcoholic beverages.